2019
DOI: 10.3390/w11030575
|View full text |Cite|
|
Sign up to set email alerts
|

The Oxygen Transfer Capacity of Submerged Plant Elodea densa in Wastewater Constructed Wetlands

Abstract: There are insufficient data for the development of process design criteria for constructed wetlands systems based on submerged plants as a major treatment agent. The aim of the study was to evaluate the oxygen transfer capacity (OTC) of E. densa, in relation to wet plants’ mass (w.m.), and the influence of E. densa on the oxygen concentration and contaminants’ removal efficiency from municipal wastewater. The obtained oxygen concentration and temperature data allowed to calculate the OTC values (mg O2·L−1·h−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…A latest research identified the macrophyte, Typha angustifolia as a possible hyper-accumulator for the elimination of Co, Cu as well as Pb from an FWS-CW using a controlled method to phytoremediation [ 193 ]. Meanwhile, the effectiveness of several other CW plants has currently been recorded, such as Zantedeschia aethiopica, Cyperus alternifolius, Heliconia burleana, Canna indica, Acorus calamus, and Ipomoea aquatic [ 194 , 195 ], including a waterlogged plant, Elodea densa, that has already demonstrated considerable capability in pollutant purification [ 196 ].…”
Section: Design and Operation Of Constructed Wetlandmentioning
confidence: 99%
“…A latest research identified the macrophyte, Typha angustifolia as a possible hyper-accumulator for the elimination of Co, Cu as well as Pb from an FWS-CW using a controlled method to phytoremediation [ 193 ]. Meanwhile, the effectiveness of several other CW plants has currently been recorded, such as Zantedeschia aethiopica, Cyperus alternifolius, Heliconia burleana, Canna indica, Acorus calamus, and Ipomoea aquatic [ 194 , 195 ], including a waterlogged plant, Elodea densa, that has already demonstrated considerable capability in pollutant purification [ 196 ].…”
Section: Design and Operation Of Constructed Wetlandmentioning
confidence: 99%
“…Within the aquatic plant species, the two pathways of O 2 transfer are: (1) internal O 2 diffusion and (2) convective‐flow. Diffusion of gases typically occurs in the root system while through‐flow a pressurized mechanism of gas transfer takes place in the rhizomes and the stems of wetland plant species (Białowiec et al, 2019, Colmer, 2003). From the atmosphere, O 2 moves from the upper part of the plants (i.e., leaves) to the lower parts (i.e., roots).…”
Section: Classification Of Cwsmentioning
confidence: 99%
“…Along with the environmental conditions (i.e., temperature, humidity), diffusion of O 2 in wetland plants is affected by the physiological (e.g., root and shoot biomass), anatomical (e.g., stems, leaves and root system) and morphological (e.g., structure, shape and size) characteristics (Colmer, 2003). In SSFCW, the movement of O 2 to the rhizosphere enhances pollutant degradation (aerobically) and the nitrification process (Brix, 2003; Białowiec et al, 2019; Yang et al, 2020). Table 3 shows the degree of importance of various functions of wetland plants based on the types of constructed wetlands.…”
Section: Classification Of Cwsmentioning
confidence: 99%
“…The presence of DO indicates the type of conditions found in the systems: aerobic, anaerobic/anoxic for biological processes [23]. Therefore, the presence of oxygen in systems with greater vegetation than in non-planted systems could be due to its release in the radical zone [24,25]. In relation to the total dissolved solids (TDS), these mainly include organic salts and residues, therefore, in terms of their decrease in treatment systems it becomes an indicator of their effectiveness [26].…”
Section: Control Parametersmentioning
confidence: 99%